Durkheim and National Identity in Ireland - Dingley, J. author. aut Link
VII, 211 p.
Keywords: This book examines the development of opposed Nationalist and Unionists identities as products of different economies, symbolically represented in religious differences, that impelled conflicting cultures and ideals of best interest that were fundamentally incompatible within a single identity.